The Role of Wedding Gifts in Bugis Customary Law in Polewali Mandar as a Legal Mechanism for the Transfer of Land Rights - Nurul Firdaus; Benny Djaja (Ekasakti Jurnal Penelitian dan Pengabdian, 2025)
Dowry is one of the components of a Bugis customary wedding ceremony. Dowry is given by man to woman as a source of livelihood for couple. In Bugis weddings, there is a term for the money used for wedding reception, called uang panaiq, and there is money for dowry, called uang mahar or sompa. Both are considered as grants or gifts without any expectation of return. Gifts for marriage can be in the form of movable or immovable property. Typically, transfers of immovable property, particularly land, as wedding gifts are conducted according to customary practices or communi-cated verbally. When documentation is provided, it is often limited to a handwritten letter rather than an authentic deed, which renders such transfers legally powerless and incomplete in formal validity. The main source of data is the Decision of the Polewali Court Number 32/Pdt.G/2024/PN POL on a dispute over land granted as a wedding gift. The results of the study based on the decision of the Polewali Mandar Regional Court judge ruled in favour of the defendant as the holder of an authentic deed in the form of a Deed of Will.